Trends in Control and Decision-Making for Human–Robot Collaboration Systems 2017
DOI: 10.1007/978-3-319-40533-9_13
|View full text |Cite
|
Sign up to set email alerts
|

Human-Collaborative Schemes in the Motion Control of Single and Multiple Mobile Robots

Abstract: Abstract-In this chapter we show and compare several representative examples of human-collaborative schemes in the control of mobile robots, with a particular emphasis on the aerial robot case. We first provide a simplified yet descriptive model of the robot and its interactions. We then use this model to define a taxonomy that highlights the main aspects of these collaboration schemes, such as: the physical domain of the robots, the degree of autonomy, the force interaction with the operator (e.g., the unilat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Shared control has been widely researched in aerial robotics [12], because it represents a promising way to accelerate the adoption of UAVs in real world applications where the presence of a human supervisor is often mandatory. Jiang et al [21] demonstrate an application of shared control in the case of a single UAV, using a hysteresis switch as a blending function.…”
Section: Related Workmentioning
confidence: 99%
“…Shared control has been widely researched in aerial robotics [12], because it represents a promising way to accelerate the adoption of UAVs in real world applications where the presence of a human supervisor is often mandatory. Jiang et al [21] demonstrate an application of shared control in the case of a single UAV, using a hysteresis switch as a blending function.…”
Section: Related Workmentioning
confidence: 99%
“…In this matter, researchers have been using haptic feedback to warn the operator about instantaneous collisions [9], [10]. Several human-collaborative schemes are compared in [11] where it is shown that haptic feedback is one of the main aspects. Among other considerations, it should be noted that the method used to generate assistive haptic cues strongly determines the usefulness of kinesthetic guidance to a large extent.…”
Section: A Related Workmentioning
confidence: 99%
“…Related Work. According to recent surveys on HSI (Kolling et al (2016)) and human multi-agent systems (Franchi (2017)), humans either take a supervisory ( Savla and Frazzoli (2012) direct ( Setter et al (2015)), shared (Franchi et al (2012)) or environmental ( Wang and Schwager (2016)) control role in an HSI framework. Our architecture however, allows humans to provide high level supervisory inputs that are also direct and detailed at the same time, thus allowing a high degree of control with lesser human effort for large swarms.…”
Section: Introductionmentioning
confidence: 99%
“…Related Work. According to recent surveys on HSI (Kolling et al (2016)) and human multi-agent systems (Franchi (2017)), humans either take a supervisory ( Savla and Frazzoli (2012)),…”
Section: Introductionmentioning
confidence: 99%